Variation in trophic resources in female South American sea lions at a small geographic scale - Grandi, Maria Florencia (2021)
Difference among colonies in the population structure of otariids can be driven by philopatry and/or by specializations in the foraging ecology of females. In northern Patagonia, the South American sea lion (SASL) shows some degree of spatial genetic structure among colonies from north and south zones. This study aims to explore the isotopic niche of SASL females in the last period of the pregnancy from different colonies of northern Patagonia and to consider whether the fine scale genetic spatial structuring is potentially related to variation in trophic resources. Stable isotope analysis was performed on 101 skin samples of newborn pups in 10 colonies, as a proxy for the feeding ecology of their mothers. Differences among colonies in the metrics studied revealed the plasticity of the species and support individual trophic specialization of SASL females at a small geographic scale. Also, significant differences were found in all isotopic metrics between the north and south zones. Several hypotheses were proposed to explain the differences in SASL females' isotope values (e.g., use of different foraging areas or prey, isotopic baseline variation). Nonetheless, further research is needed to better understand the relation between fine scale genetic structuring and the foraging ecology of SASL females.